UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS IV SDN KUNINGAN BARAT 01 JAKARTA SELATAN - Candrawati Pardiman, Artanti; Tunjungsari Sekaringtyas; Anggit Aruwiyantoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve science learning outcomes through the Discovery Learning model for fourth-grade students at SDN Kuningan Barat 01 Jakarta Selatan, consisting of 22 students. The method used is Classroom Action Research (CAR) with data collection techniques carried out through observation using teacher and student activity monitoring sheets, evaluation sheets, and documentation. The results of the study show that the Discovery Learning model can improve learning outcomes in science subjects for fourth-grade students at SDN Kuningan Barat 01 Jakarta Selatan. In the first cycle, students’ science learning achievement reached 59.09%, and in the second cycle, it increased to 90.91%, indicating an improvement of 31.82%. Based on the results of each cycle, it can be concluded that science learning using the Discovery Learning model can enhance the science learning outcomes of fourth-grade students at SDN Kuningan Barat 01 Jakarta Selatan.